EFEK RASIO TEKANAN KOMPRESOR TERHADAP UNJUK KERJA SISTEM REFRIGERASI R 141B - Selleng, Kristian (MEKTEK, 2007)
The purpose of this research is to find the effect of compressor pressure ratio with respect to performance of refrigeration system that is used refrigerant R 141B with water cooling on evaporator and condensor. The performance of refrigeration system is represented by heat transfer on evaporator and condensor.This research used experiment method. The result of this research indicates that is no effect of compressor pressure ratio to heat transfer on evaporator, on the contrary there is increasing compressor pressure ratio due to decreasing of heat transfer on condensor